The Menkes disease ATPase (ATP7A) is internalized via a Rac1-regulated, clathrin- and caveolae-independent pathway. - Cobbold, C; Coventry, J; Ponnambalam, S; Monaco, A (2003)
The Menkes disease gene encodes a P-type transmembrane ATPase (ATP7A) that translocates cytosolic copper ions across intracellular membranes of compartments along the secretory pathway. ATP7A moves from the trans-Golgi network (TGN) to the cell surface in response to exogenously added copper ions and recycles back to the TGN upon copper removal. The protein contains a C-terminal di-leucine motif necessary for internalization from the cell surface. In this study we show that ATP7A is internalized by a novel pathway that is independent of clathrin-mediated endocytosis. Expression of dominant-negative mutants of the dynamin-I, dynamin-II and Eps15 proteins that block clathrin-dependent endocytosis of the transferrin receptor do not inhibit internalization of endogenous ATP7A, or an ATP7A reporter molecule (CD8-MCF1). Similarly, inhibitors of caveolae-mediated uptake do not affect ATP7A internalization whilst preventing uptake of PODIPY-ganglioside GM(1), a caveolae marker. In contrast, expression of a constitutively active mutant of the Rac1 GTPase inhibits plasma membrane internalization of both the ATP7A and transferrin receptor transmembrane proteins. These findings define a novel route required for ATP7A internalization and delivery to endosomes.